Decolonising and indigenising attempts within tertiary education - Ann Joselynn Baltra-Ulloa; Kate Vincent (2022)
In this presentation, we detail how the social work discipline has redesigned its entire program around a decolonising and Indigenising pedagogy. We share the teaching and learning framework, how it promotes the examination of Western superiority and Whiteness in social work, and how it supports students to value the merits of decolonisation and Indigenisation. We focus on the learning and teaching practice in one particular unit within the Bachelor of Social Work with Honours and Master of Social Work (Qualifying) - HGW312/503 Social Innovation, Sustainability and Regenerative Social Work. We share how in this unit students are challenged to consider the impacts of grand challenges such as climate change and the ways social workers can respond by drawing from diverse knowledges relevant to the Australian context, including First Nations perspectives, international frameworks, and different terms of reference. We share how students respond to learning material that challenges their world view and asks them to wrestle with the uncertainty and discomfort this entails. Reflections from four years of teaching this unit will be shared, including an exploration of the triumphs and challenges involved in attempting to decolonise and Indigenise curriculum in a largely White context.